Komunikasi Antarbudaya Mahasiswa Suku Non Jawa dalam Menghadapi Culture Shock di Prodi Ilmu Komunikasi Universitas Slamet Riyadi Surakarta - Sihabuddin; Buddy Riyanto (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2026)
The background of this research is to find out the intercultural communication of non-Javanese students in facing culture shock in The Department of Communication Science at Slamet Riyadi University, Surakarta. Initially, they felt strange and foreign, and some even felt uncomfortable, but now they are very comfortable living in Solo. This study aims to gather information and analyze how non-Javanese students communicate interculturally when facing culture shock. The design of this research is qualitative with a case study approach where the results of this research are described qualitatively. Data was obtained through in-depth interviews and observations The results of the study explain that non-Javanese students feel comfortable living in Solo after experiencing culture shock which goes through four stages, namely feeling very happy to be in a new place, not feeling at home and comparing things, adapting to the new environment and feeling very comfortable in Solo like in their own hometown.